Trends in cause-specific mortality among persons with Alzheimer’s disease in South Carolina: 2014 to 2019 - Brown, Candace S.; Ning, Xi; Money, Amy; Alford, Mauriah; Pan, Yinghao; Miller, Margaret; Lohman, Matthew (Frontiers in Aging Neuroscience, 2024)
Introduction Inconsistencies of reports contributes to the underreporting of Alzheimer’s disease (AD) on death certificates. Whether underreporting exists within South Carolina has not been studied. Methods We conducted a prospective, population-based study on a cohort of persons (N = 78,534) previously diagnosed with AD and died between 2014–2019. We linked vital records with the South Carolina Alzheimer’s Disease and Related Dementias Registry to investigate their cause of death and survival rates. Descriptive analyses calculated frequencies of demographic and health-related characteristics. Turnbull’s method estimated the survival probabilities for different subgroups of patients. Hazard ratios were computed from the Cox proportional hazards model, adjusting for the following confounding variables of age at diagnosis, education level, gender, and race. Results The top immediate cause of death was Alzheimer’s disease among all racial groups, except for Native American/American Indian. More females (60.3%) were affected by AD compared to males (39.7%). There is a 25% probability of survival, beyond 5 years, after AD diagnosis. Black/African American AD patients have the smallest risk of all-cause mortality across all racial/ethnic groups (HR 0.87; 95% CI, 0.85–0.89). Individuals with lower education had a lower likelihood of mortality. Conclusion Although AD was not underreported in the state of South Carolina further research is needed to develop protocols around classification of deaths among those diagnosed with dementia and comorbidities, including cardiovascular disease, to ensure dementia is properly reported as we move to prevent and treat Alzheimer’s disease by 2025 and beyond.